2015
DOI: 10.1186/s12879-015-1330-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Flu-PRO: a patient-reported outcome (PRO) instrument to evaluate symptoms of influenza

Abstract: BackgroundTo develop content validity of a comprehensive patient-reported outcome (PRO) measure following current best scientific methodology to standardize assessment of influenza (flu) symptoms in clinical research.MethodsStage I (Concept Elicitation): 1:1 telephone interviews with influenza-positive adults (≥18 years) in the US and Mexico within 7 days of diagnosis. Participants described symptom type, character, severity, and duration. Content analysis identified themes and developed the draft Flu-PRO inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
323
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(356 citation statements)
references
References 7 publications
27
323
6
Order By: Relevance
“…Chikungunya virus (CHIKV) and dengue virus (DENV) are arboviruses currently circulating in Southeast Asia, Central and West Africa, the Pacific islands, and the Americas, and their transmission can occur simultaneously ( 1 ). DENV and CHIKV co-infections have been reported from 13 of 98 countries/territories to which the viruses are endemic and are more likely to occur in areas with high transmission intensity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Chikungunya virus (CHIKV) and dengue virus (DENV) are arboviruses currently circulating in Southeast Asia, Central and West Africa, the Pacific islands, and the Americas, and their transmission can occur simultaneously ( 1 ). DENV and CHIKV co-infections have been reported from 13 of 98 countries/territories to which the viruses are endemic and are more likely to occur in areas with high transmission intensity.…”
mentioning
confidence: 99%
“…DENV and CHIKV co-infections have been reported from 13 of 98 countries/territories to which the viruses are endemic and are more likely to occur in areas with high transmission intensity. Co-infection rates reported have ranged from 2% in Gabon to 34% in Nigeria ( 1 3 ). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two reviews respectively state that 75% (Steffen et al, 2003) and 65% (Hill, 2006) of travellers to developing countries report a degree of health impairment while abroad. More recently, a study by Vilkman, Pakkanen, Lääveri, Siikamäki, and Kantele (2016) revealed that health care was sought by 10% of overseas tourists and as many as 79% would go on to report that they fell ill while travelling. Further, in contrast with local populations, tourists are believed to be at higher risk of injury due to motor vehicle collision (McInnes, Williamson, & Morrison, 2006), and across all types of unintentional injury, are likely to experience more severe injuries (McInnes et al, 2006; Steffen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Outside of epidemiological work, some existing literature considers the health risks of travel (e.g., Jackson & Abubakar, 2017; Lüthi & Schlagenhauf, 2015), pedagogical approaches to better inform and prepare tourists for such risks (e.g., Marchand, Merrina, Gagnayre, & Bouchaud, 2017; Seale et al, 2016), and outcomes of this education (e.g., Angelin, Evengård, & Palmgren, 2014; Croughs, Remmen, & Van den Ende, 2014). Such work aims to contextualize the assumption that a confluence of “appropriate pre‐travel advice and patient compliance are … key elements in ensuring that world travelers return home in good health” (McIntosh, 2015, p. 143).…”
Section: Introductionmentioning
confidence: 99%